Observations of Nutrient Supply by Mesoscale Eddy Stirring and Small‐Scale Turbulence in the Oligotrophic North Atlantic. Issue 12 (17th December 2021) - Spingys, Carl P.; Williams, Richard G.; Tuerena, Robyn E.; Naveira Garabato, Alberto; Vic, Clément; Forryan, Alexander; Sharples, Jonathan
Abstract: Sustaining biological export over the open ocean requires a physical supply of nutrients to the mixed layer and thermocline. The relative importance of diapycnal mixing, diapycnal advection, and isopycnal stirring by mesoscale eddies in providing this nutrient supply is explored using a field campaign in oligotrophic waters in the subtropical North Atlantic, consisting of transects over and off the mid‐Atlantic ridge. Eddy stirring rates are estimated from the excess temperature variance dissipation relative to the turbulent kinetic energy dissipation, and using eddy statistics from satellite observations combined with 9‐month‐long mooring data. The vertical nutrient fluxes by diapycnal mixing, diapycnal advection, and isopycnal mesoscale eddy stirring are assessed using nitrate measurements from observations or a climatology. Diapycnal mixing and advection provide a nutrient supply within the euphotic zone, but a loss of nutrients within the upper thermocline. Eddy stirring augments, and is comparable to, the diapycnal transfer of nutrients within the summertime upper thermocline, while also acting to replenish nutrients within the deeper parts of the thermocline. The eddy supply of nitrate is relatively small in the center of the subtropical gyre, reaching up to 0.06 mol N m −2 yr −1, but is likely to be enhanced on the flanks of the gyre due to larger isopycnal slopes and lateral nitrate gradients. The nutrient supply to the euphotic zone is achieved via a multistage mechanism: a diapycnal transfer of nutrients by small‐scale turbulence to the euphotic zone, and an isopycnal stirring of nutrients by mesoscale eddies replenishing nutrients in the upper thermocline. Plain Language Summary: Phytoplankton growth requires a supply of nutrients to the base of the euphotic zone, which is usually provided by a combination of vertical mixing or vertical upwelling of nutrients. However, in the oligotrophic waters of the central North Atlantic, it is unclear how the vertical supply of nutrients is sustained. Here, we use field data to explore the roles of mixing across density surfaces, advection across density surfaces and mesoscale eddy stirring along density surfaces in supplying nutrients to some of the most nutrient‐depleted surface waters in the central North Atlantic. Diapycnal mixing and advection are found to be important in supplying nutrients to the euphotic zone during summer, but at the expense of eroding the nutrients in the upper thermocline. In contrast, mesoscale eddy stirring augments the diapycnal supply of nutrients to the euphotic zone and replenishes nutrients in the upper thermocline. Key Points: Diapycnal mixing and advection and mesoscale eddy stirring supply nutrients to some of the most oligotrophic waters in the North Atlantic Diapycnal loss of nutrients below the seasonal boundary layer is partly replenished by eddy stirring in the upper thermocline Relay race of nutrient supply by eddy stirring to the upper thermocline passed on by diapycnal mixing and advection to the euphotic zone